Like mother, like child? Sex differences in the maternal transmission of offending among a Scottish cohort of pre-adolescent children - Jahanshahi, Babak (Criminology & criminal justice, 2023)
That parental offending acts as a strong risk factor for offending in children is well-established within criminology. Yet, research on maternal offending is relatively limited, even though many women take on a significantly higher share of childcare responsibilities, and as such, might reasonably be expected to exert an especially strong influence on their children. In part, this lacuna might be attributed to a male-centric lens within criminology, which has tended to overlook female offending. Aimed in part at redressing this imbalance, this article investigates the maternal transmission of offending among a cohort of 12-year-olds, using self-report data from the longitudinal Growing Up in Scotland study. The analysis shows that intragenerational maternal offending acts as a significant predictor of offending among daughters, but that intergenerational offending does not. We found no significant relationship between mothers’ offending and sons’, who appear more vulnerable to a range of wider risk factors.